On the role played by anticommutativity in Leibniz algebras - Kurdachenko, L.A.; Semko, N.N.; Subbotin, I.Ya. (Reports of the National Academy of Sciences of Ukraine, 2019)
Lie algebras are exactly the anticommutative Leibniz algebras. We conduct a brief analysis of the approach to Leibniz algebras which is based on the concept of anticenter (Lie-center) and antinilpotency (Lie nilpotentency).